The Concept of Musical Nationalism in Compositional Creativity: A Theoretical Aspect - Габріела Асталош (Культура і мистецтво у сучасному світі)
The aim of the article is to reveal the essence of the concept of musical nationalism and the principles of its manifestations in professional compositional creative work. Results. The need for national identity, the desire to express oneself, and the focus on uniqueness drive humanity towards creating certain products of activity in the scientific, research, and creative spheres, collectively shaping the patriotic mentality of the entire nation. Every conscious artist who aims to lobby for national content in the socio-cultural and even political space through his creative work appeals to factors that are reproduced in the audience’s imagination as a symbol, code of the nation. The search for means and forms of expressing originality based on national characteristics, and the desire for cultural autonomy via the reproduction and artistic reinterpretation of typical features, mythology, mentality, folklore, etc. create traditions of the national style. The way this paradigm is expressed depends on the depth of experience of national issues by the author of an art work. Musical nationalism becomes the highest degree of realisation of the national idea in creative work, forms a unique concept, a content of which consists in conscious and purposeful reproduction by artists by means of music of bright national-mental attributes, values, ideas, thinking patterns and philosophising, psycho-emotional characteristics, temperament, world perception, and worldview, etc. Scientific novelty. For the first time in the history of Ukrainian art studies, the term “concept of musical nationalism” is introduced into scholarly discourse, and its meaning and the expediency of its use are explained. Conclusions. The professional musical art of any country becomes a reflection of the cultural heritage of the nation, and is based on the synthesis of the artistic content of the art sample, its emotional message, and those specific means of expression that are most capable of revealing the context of the work. One of the most distinctive identifiers of compositional creativity is the national factor, manifested by the artist in presenting characteristic features of the local society, certain archetypes, and traditions, which are originally interpreted in his heritage. A conscious, purposeful approach to the ideological content of music is the result of the author's creative reflection, a reflection through the prism of his own stylistic preferences and priorities of a number of national ideals, national dreams, centuries-old aspirations of his native people influenced by specific historical and political factors. All this forms the concept of musical nationalism.